The Analysis of Swear Words Used by the Children in Poh Bergong Village - Saniada, Komang Nova; Ramendra, Dewa Putu; Mahendrayana, Gede (International Journal of Language and Literature, 2023)
The phenomenon of using swears words are often found in rural areas in Bali. Even the phenomenon of using swears words are also widely used by children who are inappropriate in the social context of society. This research aimed to analyze the forms, types, and functions of swear words that used by children in Poh Bergong Village. Descriptive qualitative method was used as a design to investigate the study in this research and gain the data from the children. The subjects in this study were the children in Poh Bergong Village who used swear words in their daily life. The subjects had an age range of about 6 until 11 years. The objects of this study were the swear words that were used by children in Poh Bergong Village. The data were collected through observation and interview. Observation was used in the social sciences as a method for collecting data about people, processes, and cultures. Interview was used to collect the information about swear words used and the reason why the children use swear words in communication. In this research, there were five instruments used to collect the data, that were researcher, voice recorder, notebook, observation sheet, and interview guide. Qualitative Data Analysis (QDA) in the form of descriptive was used as a means to analyze data obtained by the researcher. The result showed that the swear words used by children in Poh Bergong Village has eighty-three forms of swear words,eleven types of swear words, and six functions of swear words.